Andirons from Khanbulag (Republic of Azerbaijan) - Kirichenko, Dmitriy; Aghalarzade, Anar (Revista Arheologică, 2026)
The article deals with the samples of the ceramic wares – movable hearths. These artifacts were accidentally discovered during agricultural works in the yard of a local resident of the Khanbulag village (Yardımli district, Azerbaijan Republic). After examining the site, the authors of this article concluded that there was a multilayered settlement. Unfortunately, the cultural layer was almost completely destroyed and the materials were in a mixed form. This process is not surprising, taken into account the long-term and continuous agricultural work in the area. The discovered artifacts belong to three historical periods: the Early Bronze Age, Antiquity and the Middle Ages. The six fragments of clay hearths were presented to us for scientific analysis. According to the accepted classification, the objects were used locally as hearth stands in the shape of a “horseshoe”. The artifacts are well decorated (with incisions, “signs”, circular marks and applied motifs), have zoomorphic ends in the form of a ram’s head and a ram. The objects were handmade and well fired. The color shades of the andirons vary, but are mainly brown. Movable hearth stands of this type have similarities with other objects from the South Caucasus, Eastern Anatolia, north-western Iran and the Southern Levant. All clay andiron fragments examined in this article symbolized the image of a ram’s head/ram to one degree or another. Such clay hearth stands, which were horseshoe-shaped and could be transported, were mainly found in the western territory of the Kura-Araxes cultural-historical community. The artifacts from Khanbulag expand the range of such items among the Kura-Araxes tribes to the east and are currently considered the only finds discovered in the southeastern region of the Republic of Azerbaijan.